Exploring students ' conceptions of collaborative information use and information use outcomes in credit-based group learning assignments - Ndumbaro, Faraja (University of Dar es Salaam Library Journal, 2019)
The purpose of this study was to explore students ' conceptual understanding of collaborative information use (CIU) and information use outcomes in the context of credit-based group learning assignments. The study comprised of forestry and architecture undergraduate students from SUA and ARU respectively. Qualitative research design and ethnographic case study research method were used. Study population consisted of 12 groups, 8 from SUA and 4 from ARU. Six groups, two groups from ARU and four from SUA were purposively selected. The Study was carried out for the period of six weeks. Data were collected using observations and Focus Group Discussions. The results indicate multiple conceptions of information use (IU) and information use outcomes. Students ' understandings of IU and information use outcomes reflect characteristics of information sources used, learning tasks objectives and tasks dynamics. The study has contributed to deep understanding of different constituents of IU and information use outcomes and the role of information in supporting students ' collaborative learning process.